Primate-specific Long Non-coding RNAs and MicroRNAs - Awan, Hassaan Mehboob (Genomics Proteomics Bioinformatics, 2017)
Non-coding RNAs (ncRNAs) are critical regulators of gene expression in essentially all life forms. Long ncRNAs (lncRNAs) and microRNAs (miRNAs) are two important RNA classes possessing regulatory functions. Up to date, many primate-specific ncRNAs have been identified and investigated. Their expression specificity to primate lineage suggests primate-specific roles. It is thus critical to elucidate the biological significance of primate or even human-specific ncRNAs, and to develop potential ncRNA-based therapeutics. Here, we have summarized the studies regarding regulatory roles of some key primate-specific lncRNAs and miRNAs.